Dietetic treatment of digestive disease - Criss, Ella (My University, 1904)
Introduction: The correct feeding of persons in perfect health is of very great importance, but when disease takes possession of the body then the food consumed becomes a question of supreme importance. It is said by learned doctors that over half of all disease is based upon errors of diet. Drugs are used less at the present day than ever before as the physicians realize that recovery to health from an attack of disease is a natural process and the drugs are only to assist nature in effecting a cure. The unperverted appetite, in health, is generally a safe guide as long as only plain simple foods are taken, but when diseased conditions enter in, it must not be followed. The nature of the disease must be studied; then the foods administered to correspond with the needs caused by the disease. The kind and quantity of food will vary according to the portion of the body affected…
Citation: Criss, Ella. Dietetic treatment of digestive disease. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Diet; Disease; Stomach Diseases; Disease Treatment; Theses; Manuscripts (documents)